2018
DOI: 10.15761/iod.1000209
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of factors associated with poor glycemic control among patients with Type II Diabetes mellitus

Abstract: Background: Glycemic control remains the major therapeutic objective for prevention of target organ damage and other complications arising from diabetes. In addition, elucidation of various determinants of poor glycemic control may contribute to a clearer understanding of modifiable antecedents of diabetes-related complications and help to achieve improved diabetic control and patient outcomes.Method: Two hundred twenty patients of Type II diabetes mellitus were taken after Informed consent. Patients who fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
23
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 10 publications
11
23
1
3
Order By: Relevance
“…Diabetic patients who have good dietary adherence were 2.4 times more likely to have good glycemic control as compared with those who have poor dietary adherence. This finding is consistent with the study conducted at Suluh Hospital, Ethiopia and India [ 18 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Diabetic patients who have good dietary adherence were 2.4 times more likely to have good glycemic control as compared with those who have poor dietary adherence. This finding is consistent with the study conducted at Suluh Hospital, Ethiopia and India [ 18 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…The result of this study showed that the level of glycemic control among type II diabetic patients is 71.4% which is consistent with the finding at Dessie Referral Hospital (70.8%), Jimma University Teaching Hospital (70.9%), Turkey (67.5), Myanmar (72.1%), and Saudi Arabia (74.9%) [ 12 , 20 , [30] , [31] , [32] ]. On the other hand, it is below than the study conducted at Tikur Anbessa Hospital (80%), South Africa (83.8%), Kenya (81.6%), India (91.8%), and Palestine (80.5%) [ [33] , [34] , [35] , [36] , [37] ]. On the other hand, it is higher than the study done at Zambia (61.3%), Limmu Genet Hospital (63.8%), Suhul Hospital (63.5%), Nigeria (55%), Ayider Specialized hospital (48.7%) and Shenen Gibe Hospital (59.2%) [ 21 , [38] , [39] , [40] , [41] , [42] ].…”
Section: Discussionmentioning
confidence: 80%
“…Diabetic patients who can read and write, learnt primary school and achieve college and above educational status are 3, 4 and 5.7 times more likely to have good glycemic control as compared with those who couldn't read and write respectively. This is consistent with study conducted at Dessie Referral Hospital, Jimma University Teaching Hospital and Shenen Gibie Hospital [20,21,[30][31][32][33][34][35][36][37][38][39]. The reason might be educational status may affect patients adherence to medical recommendations.…”
Section: Discussionsupporting
confidence: 85%
“…The result of this study showed that the level of glycemic control among type II diabetic patients is 71.4% which is consistent with the study done at Dessie Referral hospital (70.8%), Jimma University teaching Hospital (70.9%), Turkey (67.5), Myanmar (72.1%), and Saudi Arabia (74.9%) (12,20,(30)(31)(32). Whereas it is below than the study conducted at TikurAnbessa hospital (80%), South Africa (83.8%), Kenya (81.6%), India (91.8%) and Palestine (80.5%) (33)(34)(35)(36)(37).On the other hand, it is higher than the study done at Zambia (61.3%), Limmu Genet Hospital (63.8%), Suhul Hospital (63.5%), Nigeria (55%), Ayider Specialized hospital (48.7%) and Shenen Gibe Hospital (59.2%) (21,(38)(39)(40)(41)(42). The possible justification for the discrepancy might be the difference in quality of care given for the patients in different hospitals that studies were conducted and the method used to assess the glycemic level.…”
Section: Discussionmentioning
confidence: 65%
“…This discrepancy might be due to the study population characteristics, study design and the kind of medication they were given. Besides, the pooled prevalence of poor glycemic control among diabetic patients is lower than a study conducted in Bangladish 82% (19), manipal/India 78.2% (20), 78.6% , Kenya 91.8% (21), Saudi Arabia 74.9% (22). This variation could be due to the measurement tool used for the outcome determination.…”
Section: R E S I D E N C Ementioning
confidence: 71%